Metabolomics: a promising tool for deciphering metabolic impairment in heavy metal toxicities - Akash, Muhammad Sajid Hamid; Yaqoob, Azka; Rehman, Kanwal; Imran, Muhammad; Assiri, Mohammed A.; Al-Rashed, Fatema; Al-Mulla, Fahd; Ahmad, Rasheed; Sindhu, Sardar (Frontiers in Molecular Biosciences, 2023)
Heavy metals are the metal compounds found in earth’s crust and have densities higher than that of water. Common heavy metals include the lead, arsenic, mercury, cadmium, copper, manganese, chromium, nickel, and aluminum. Their environmental levels are consistently rising above the permissible limits and they are highly toxic as enter living systems via inhalation, ingestion, or inoculation. Prolonged exposures cause the disruption of metabolism, altered gene and/or protein expression, and dysregulated metabolite profiles. Metabolomics is a state of the art analytical tool widely used for pathomolecular investigations, biomarkers, drug discovery and validation of biotransformation pathways in the fields of biomedicine, nutrition, agriculture, and industry. Here, we overview studies using metabolomics as a dynamic tool to decipher the mechanisms of metabolic impairment related to heavy metal toxicities caused by the environmental or experimental exposures in different living systems. These investigations highlight the key role of metabolomics in identifying perturbations in pathways of lipid and amino acid metabolism, with a critical role of oxidative stress in metabolic impairment. We present the conclusions with future perspectives on metabolomics applications in meeting emerging needs.